2019
DOI: 10.1111/1467-8551.12358
|View full text |Cite
|
Sign up to set email alerts
|

How and When Servant Leaders Enable Collective Thriving: The Role of Team–Member Exchange and Political Climate

Abstract: Thriving teams are critical to the effective functioning of an organization. Extending Spreitzer et al.'s (2005) socially embedded model of thriving at work to the team level, this study explores how and when servant leadership promotes collective thriving. Through data collected from 80 teams composed of 520 employees, the study reveals that servant leaders help embed members in high-quality team-member exchange relationships, which in turn enables their collective thriving. The authors find that a highly pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 78 publications
0
35
0
Order By: Relevance
“…Servant leadership places importance on teamwork and building relationships. That is, it promotes the development of value-based management, creating conditions to enable the company to move forward as much as possible [117,118]. Furthermore, if servant leadership is used efficiently, each organization member can use their own skills and experience as much as possible.…”
Section: Servant Leadershipmentioning
confidence: 99%
“…Servant leadership places importance on teamwork and building relationships. That is, it promotes the development of value-based management, creating conditions to enable the company to move forward as much as possible [117,118]. Furthermore, if servant leadership is used efficiently, each organization member can use their own skills and experience as much as possible.…”
Section: Servant Leadershipmentioning
confidence: 99%
“…For example, Khan et al (2015) identified "involvement culture" as a moderator of servant leadership in the prediction of workplace spirituality. More recently, Xu and Wang (2020) identified political climate in organizations as a factor that impacts the beneficial effect of servant leadership on collective thriving. Furthermore, in their systematic review of servant leadership, Eva et al (2019) suggested that culture could be an organizational factor that impacts the "display" of servant leadership behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Servant leaders offer their social network to benefit their subordinates (Parris & Peachey, 2013). In addition to providing career growth opportunities, servant leaders enable employees to broaden their social horizons by sharing their power with them (Xu & Wang, 2020). The distinguishing feature of servant leaders is that they consider themselves servants whose ultimate goal is to serve employees (Karatepe et al, 2019).…”
Section: Servant Leadership Social Power and Subjective Career Successmentioning
confidence: 99%